2010
DOI: 10.1080/13854046.2010.528452
|View full text |Cite
|
Sign up to set email alerts
|

Operating Characteristics of Executive Functioning Tests Following Traumatic Brain Injury

Abstract: The primary purposes of this study were to determine if controls, mild, and moderate/severe traumatic brain injury (TBI) patients performed differently on a battery of executive functioning (EF) tests, and to identify the operating characteristics of EF tests in this population. Participants consisted of 46 brain injured individuals and 24 healthy controls. All participants completed an extensive battery of EF tests. Results showed that mild TBI participants performed worse than controls on the Trail Making Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
(44 reference statements)
2
23
0
1
Order By: Relevance
“…The domain of executive functions is particularly important in assessing people who have sustained traumatic brain injury (TBI), because these deficits are common in this population, due in part to susceptibility of the frontal lobe to focal injury and in part to TBI mechanisms such as traumatic axonal injury, which inherently cause diffuse, widespread lesions (Bigler, 2007;Li & Feng, 2009). Studies have indicated a dose-response relationship between injury severity and performance on executive function measures (Demery, Larson, Dixit, Bauer, & Perlstein, 2010;Ord, Greve, Bianchini, & Aquarrevere, 2010). That is, individuals with complicated mild to severe TBI performed consistently worse than healthy controls, with worse performance associated with variables characterizing injury severity, such as length of coma and intracranial lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The domain of executive functions is particularly important in assessing people who have sustained traumatic brain injury (TBI), because these deficits are common in this population, due in part to susceptibility of the frontal lobe to focal injury and in part to TBI mechanisms such as traumatic axonal injury, which inherently cause diffuse, widespread lesions (Bigler, 2007;Li & Feng, 2009). Studies have indicated a dose-response relationship between injury severity and performance on executive function measures (Demery, Larson, Dixit, Bauer, & Perlstein, 2010;Ord, Greve, Bianchini, & Aquarrevere, 2010). That is, individuals with complicated mild to severe TBI performed consistently worse than healthy controls, with worse performance associated with variables characterizing injury severity, such as length of coma and intracranial lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Severe TBI survivors suffer from physical, functional, cognitive, and psychosocial disabilities. [4] So, involvement of families in rehabilitation and need for family intervention is recommended in the trauma care setting. [5] The caregivers play significant role in taking care of the patient, recovery, and rehabilitation of TBI survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Um es tudo recente de Israel encontrou que 87% da amostra de TcE crônico apresentou desempenho prejudicado nos escores de fluência verbal semântica e 70% na fluência verbal fonêmica-ortográfica (Kavé, Heled, Vakil & Agranov, 2011). Demery, Larson, Dixit, Bauer & Perlstein (2010) encontrou 54% da amostra de TCE moderado a grave desempenhando-se dentro do esperado em tarefas de atenção concentrada, flexibilidade cognitiva e memória de trabalho (38% desses mesmos pacientes com desempenho adequado na parte A do Teste das Trilhas (TT) e 27% com desempenho adequado na parte B do TT). Ainda, 65% dos mesmos pacientes desempenharam-se bem em uma tarefa de Span de Dígitos (ordem indireta).…”
Section: Introductionunclassified